ANALISIS MATEMATIKA PADA PENYEBARAN VIRUS NIPAH (NiV) DENGAN MENGGUNAKAN KENDALI OPTIMAL METODE Pontryagin Maximum Principle (PMP) - Sitti Rosnafi’an Sumardi; Cecilia Bintang Girik Allo; Winda Ade Fitriya B; Nicea Roona Paranoan (KOLONI, 2023)
Nipah virus (NiV) is a virus that can be transmitted. This journal discusses the use of optimal control strategies to minimize populations or individuals infected with the NiV virus. We developed a mathematical model for the spread of Nipah vision (NiV) with two control strategies, namely community awareness and treatment. The aim of this study is to minimize the number of infected individuals and to reduce the costs required to create awareness and treatment at set time intervals. To achieve this goal the authors use the Pontryagin Maximum Principle (PMP) method. To see the effectiveness of using the optimal control strategy, the authors use the Runge Kutta Order 4 method (RK 4: Forward & Backward). The results of the simulation show that using two controls (public awareness and treatment) can optimally reduce the number of individuals infected with Nipah virus (NiV). Keywords: Optimal Control, Infectious Diseases, Nipah Virus, PMP, Runge Kutta Order 4